Surface modification of TC4 Ti alloy by laser cladding with TiC＋Ti powders - 张可敏 邹建新 李军 于治水 王慧萍 (Transactions of Nonferrous Metals Society of China, 2010)
Laser surface cladding was applied on a TC4 Ti alloy to improve its surface properties. Mixed TiC and Ti powders with a TiC-to-Ti mass ratio of 1：3 were put onto the TC4 Ti alloy and subsequently treated by laser beam. The microstructure and composition modifications in the surfaee layer were carefully investigated by using SEM, EDX and XRD. Due to melting, liquid state mixing followed by rapid solidification and cooling, a layer with graded microstructures and compositions formed. The TiC powders were completely dissolved into the melted layer during melting and segregated as fine dendrites when solidified. The inter-dendritic areas were filled with fine a＇ phase lamellae enrich in A1. Mainly due to the reduced TiC volume fraction with increasing depth, the hardness decreases with increasing depth in the laser clad layer with a maximum value of HV1400, about 4.5 times of the initial one.